Analisis Kesalahan Umum dalam Penerjemahan Berita Arab pada Situs Wesite - Luthfi Anisatin; Salma Salma; Muhammad Hanif Abdillah (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2023)
This study aimed to determine the forms of errors in the translation of Arabic news texts and translation methods that are often used so that improvements are needed in translation results. The urgency of this research is based on the nature of translation that is not just mastering the source language (Bsu) and target language (Bsa), But also mastering translation theory so as to produce effective and efficient translation. This research uses a descriptive qualitative approach with literature analysis techniques (library research) through analysis of word structure (syntax), sentence structure (morphology), discourse structure, and semantic structure. Based on the analysis of common errors in the translation of Arabic news on the website, several errors were made, this is based on the used of translation methods that need attention again. Based on the results of the analysis, it shows that many translation errors are caused by translation that is too focused by referring to one of the translation methods, including the word-for-word translation as in sentences مدير الأمن العام interpreted as “kepala keamanan umum” The truth is “direktur keamanan publik”, literal translation as in sentences التاسع من ذي حجة interpreted as “yang kesembilan dari Dzulhijjah” the truth is “tanggal sembilan Dzulhijjah”, faithful translation as in sentences وأيدينا طويلة interpreted as “dan tangan kita panjang” the truth is “kami siap menolong”, and semantic translation as in the word النفرة interpreted as “nafra” the truth is “lempar jumrah”.